EKSPLORASI PEMANFAATAN RUANG TONGKONAN BERDASARKAN PERSPEKTIF MASYARAKAT TORAJA TERHADAP GENDER - Veronica, Selly; Aulia, Afina Nisa (Universitas Medan Area, 2024)
The way a traditional society's culture views gender roles will influence the behavior of that society in the built environment, including the traditional Toraja society. Yet, in contrast to other traditional societies, this society believes that men and women have equally important roles in building family life or what is usually called gender equality. Thus, this research was conducted to see how gender equality influences people's behavior in their daily lives, especially from an architectural perspective which is reflected in spatial patterns. Therefore, this research was carried out by applying a qualitative descriptive method, where data was obtained through literature study and direct observation in the field, and strengthened by the results of interviews with the local community. The data is then processed and explained based on aspects: house ownership, roles and activities of each gender, use of space, and gender symbolization in the physical form of traditional Toraja house buildings or what is called Tongkonan. The research results show that the ancient life patterns of the Toraja Indigenous People who adhere to gender equality are manifested in patterns of spatial planning and use of space. Even though Tongkonan is considered an image of women as mothers, there was no special treatment or inclusion of certain genders in utilizing every corner of the existing space.